BNP/NT-proBNP in pulmonary arterial hypertension: time for point-of-care testing? - Robert A. Lewis; Charlotte Durrington; Robin Condliffe; David G. Kiely (European Respiratory Review, 2020)
Despite the advent of new therapies and improved outcomes in patients with pulmonary arterial hypertension (PAH), it remains a life-shortening disease and the time to diagnosis remains unchanged. Strategies to improve outcomes are therefore currently focused on earlier diagnosis and a treatment approach aimed at moving patients with PAH into a category of low-risk of 1-year mortality. B-type natriuretic peptide (BNP; or brain natriuretic peptide) and N-terminal prohormone of BNP (NT-proBNP) are released from cardiac myocytes in response to mechanical load and wall stress. Elevated levels of BNP and NT-proBNP are incorporated into several PAH risk stratification tools and screening algorithms to aid diagnosis of systemic sclerosis. We have undertaken a systematic review of the literature with respect to the use of BNP and NT-proBNP in PAH and the use of these biomarkers in the diagnosis and risk stratification of PAH, their relation to pulmonary haemodynamics and the potential for point-of-care testing to improve diagnosis and prognosis.